Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Coffeeshop “XYZ” Kota Pekanbaru - Wicara, Dinda Genta (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The aim of this study is to find out the impact of Service Quality on Customer Satisfaction on Coffeeshop XYZ City Pekanbaru. To that goal, the research was conducted using a sample of 100 people, using simple random methods. (accidental random sampling). Data analysis methods use simple linear regression. Basing the t test results partially obtained that t-count is larger than t-table (12,711 > 1,984). Thus it can be concluded that the service quality variable has a positive and significant influence on consumer satisfaction on Coffeeshop XYZ Kota Pekanbaru. The R. Square (R2) value of 0.622 (62.2%) explains that the service quality variable contributes an influence on consumer satisfaction on Coffeeshop XYZ City Pekanbaru by 62.2%. The remaining 37.8% describes other free variables not observed in this study. Recommendations that can be submitted are expected that the company pay attention to employees of Coffeeshop XYZ Kota Pekanbaru have expertise in using aiding tools in the service process as this gets the lowest response from respondents